Proton conducting electrolytes composed of chondroitin sulfate polysaccharide and citric acid - Santos, Filipe M. (2020)
Novel electrolytes composed of chondroitin sulfate A (CSA) and citric acid (CA) have been prepared using a clean, safe, and fast route. These electrolytes exhibit different physical-chemical properties, depending on the amount of CA. For X > 82.3%, where X is the mass ratio, in %, of CA/(CA + CSA), whitish polycrystalline powders result. Lower amounts of CA leads to the production of translucent, amorphous films, sticky for X = 75.6 and 82.0, brittle for X < 43.6 and crack-free, self-standing for 43.6 < X < 75.6%. The results obtained provide evidence that, at low pH, strong hydrogen bonding interactions take place between the anionic sulfonic and carboxylic groups of CSA and CA. CA exerts a key role, acting as a cross-linker and proton source, while simultaneously influencing sample morphology. At room temperature the highest ionic conductivity is achieved at X = 60.8%. A significant enhancement of the ionic conductivity of this sample occurs with the increase of relative humidity (RH) (from 3.1 x 10(-7) to 3.7 x 10(-2) S cm(-1) 30% for RH = 30 and similar to 100%, respectively).